ANALISIS PENENTUAN STRATEGI PEMASRAN YANG TEPAT GUNA MENINGKATKAN POSISI PERSAINGAN PASAR PRODUK PAKAN IKAN PADA PT CENTRAL PROTEINA PRIMA TBK KIM II MABAR DELI SERDANG - Arya, Muhammad Dicky; Nasution, Lukman (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2021)
Marketing strategy is important to measure the success of a business. This study aims to determine the marketing strategy and constraints in increasing the competitive position of the market for fish feed products at PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang. The type of research used is descriptive qualitative research.the informants in this study were marketing and consumers from PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang The results of this study indicate that PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang has implemented a marketing mix strategy that uses 4P variables, namely Product, Price, Place and Promotion which is able to increase the sales volume of PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang. In this study, there are also supporting and inhibiting factors for implementing marketing strategies on the sale of fish feed products at PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang. The supporting factors are quality products, strategic locations and technology used. While the inhibiting factors for marketing strategies for fish feed products at PT. Central Proteina Prima Tbk KIM II Mabar Deli Serdang, namely promotions that have not been maximized and illegal fees often occur by irresponsible elements to suppliers.